Iowa RBA, January 1-4, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for January 1-4, 1996. Highlights of the update include sightings of a Great Black-backed Gull, Lesser Black-backed Gull, Thayer's Gull, Glaucous Gull, Yellow-rumped Warblers and a Snowy Owl. Also included are handwritten notes for the next week's update with sightings of Hooded Mergansers, Pied-billed Grebes and a Wood Duck. Epson - sheet feed/flatbed